KOMUNIKASI EMPATIK BERBASIS PENDIDIKAN ISLAM PADA PROGRAM GCKI DALAM PENANGANAN KASUS BULLYING DI SMA BOGOR - Pambayun, Ellys Lestari; Sugiarto; Anis Khosyatunnisa Raujanah; Tiara Dianita Chaeruddin; Meilita Hindia Sari (SYAIKHONA: Jurnal Magister Pendidikan Agama Islam, 2024)
This study discusses the implementation of Islamic-based empathic communication in the GCKI (Indonesian Smart Communication Movement) program as a strategy for handling bullying cases at Al-Basyariah High School Bogor. Using a case study method, this study analyzes how empathic communication, both cognitive and affective, can be applied in an educational context to create a more inclusive and safer environment for students. Cognitive empathic communication theory emphasizes understanding the perspective of others, while affective empathic communication focuses on emotional resonance and concern for the feelings of others. The Islamic approach reinforces the moral and ethical values that underlie social interaction, emphasizing the importance of compassion, justice, and mutual respect. The results of the study show that the application of Islamic-based empathetic communication in the GCKI program at Al-Basyariah High School in Regency Bogor succeeded in reducing bullying incidents, increasing students' awareness of the impact of bullying, increase students' awareness of the impact of negative behavior, as well as build solidarity among them. This finding is expected to be a reference for other schools in developing more effective anti-bullying programs.